Export orientation of Indonesia’s manufacturing industry - Fitra Basri, Ramadhani; Karimi, Syafruddin; Zulkifli, Zulkifli (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
The aim of this study is to analyze the export orientation of the manufacturing industry sector in Indonesia. In order to achieve this objective, Cobb-Douglas production function, consisting of foreign direct investment (FDI) and labor, was developed. The data from the Industrial Survey conducted by the Central Bureau of Statistics (Badan Pusat Statistik/BPS) for the period 2005-2015 with 249 manufacturing companies as samples. Based on the Hausman test, the fixed-effect model is more appropriate to be used in this study. The results from the estimation indicate that FDI and labor have a positive and significant impact on the growth of the export manufacturing industry. Labor has a stronger effect on exports than on FDI, where the coefficient of labor is 3.696 and of FDI is 0.302. On the basis of this result, it could be concluded that FDI and labor lead the export orientation to the Indonesian manufacturing industry.